Placing survival above the ideal of motherhood: experiences of migratory mourning of migrant mothers in Chile - Lucia Castillo Lobos; Luis Patricio Contreras Vásquez; Elizabeth Yenny Hermosilla Aldea (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
This article presents an approach to the phenomenon of migratory mourning of migrant mothers in Chile. Between 2021 and 2022, a qualitative exploratory study based on symbolic interactionism was carried out, in which semi-structured interviews were conducted with 39 migrant mothers of Venezuelan (18), Peruvian (11) and Haitian (9) origin. Based on a theoretically-informed thematic analysis, three analytical categories emerged: 1) the loss of social ties and distance to their place of origin; 2) expectations versus reality; and 3) the validation of overexertion. Migrant mothers express migratory mourning with varying levels of nuance depending on their country of origin, and to a greater or lesser degree signify their experiences in terms of uprooting and the absence of support networks, which they identify as the main cause of the sadness they experience on a daily basis. This sadness increases when they negotiate their ideals regarding the upbringing of their sons and daughters in favor of material subsistence in order to achieve the goals of a better life, and for which they justify overexertion as a strategy for improvement. These pressures bring with them psychological and physical consequences and interfere with their processes of migratory mourning, compromising their mental health and that of their children.